Sociopreneurship and Philanthropy during Pandemic COVID-19: A Matchmaker Idea - Dwi Prasetyani; Amelia Choya Tia Rosalia; Rizky Nur Ayuningtyas Putri (Universitas Muhammadiyah Ponorogo, 2022)
The current economic situation is dire because of the Covid-19 pandemic, which has increased unemployment, reduced income, and reduced people's well-being. Many social issues become homework that necessitates real-world solutions. The 1.12 million increases in the number of poor people in 2021 is a clear indication of the need for steps to address social needs that are not being met by the private sector or the government. This study aims to conduct a literature review on the concept of sociopreneurship in general, as well as to investigate the role of sociopreneurship and Philanthropy in mitigating the effects of the Pandemic's economic downturn. Sociopreneurship, which places priority on social advantages without compromise on material gains and philanthropy, has more positive impacts than if the two were to take place separately. The findings show that sociopreneurship is a type of entrepreneurial initiative that can be developed with the primary goal of assisting the community, and that philanthropy plays an important role in supplementing government programs by providing community contributions and solidarity aimed at reviving economic activity.